Antibacterial Activity and Sensory Characteristics of Low Calories Functional Candy Contains Trigonas Honey (Trigona Itama) and Patchouli Oil (Pogostemon Cablin Benth) - Juliani, Juliani; Irmayanti, Irmayanti; AK, M Daud (Universitas Syiah Kuala, 2022)
Candy is a product made from sugar which can cause health problems. The proportion of sugar with high calories can be replaced with isomalt which is low in calories, and honey which is beneficial to health. In addition, the use of synthetic flavours in candy can be replaced with essential oils such as patchouli oil. Product analysis was in the form of salivary bacterial growth inhibition and hedonic organoleptic tests to determine the samples' antibacterial activity and sensory characteristics. This research was conducted using two factors of a sugar formulation consisting of 3 levels, namely, G1, G2, and G3. The second factor was patchouli oil concentration consisting of 4 levels, namely N1, N2, N3, and N4. Data on the results of the antibacterial and hedonic activity tests were analyzed using a factorial, Completely Randomized Design (CRD). From the analysis of variance, it can be concluded that sugar formulation, patchouli oil concentration, and their interactions had a significant effect (P0.05) on the growth of salivary bacteria, patchouli oil concentration had a significant effect (P0.05) on hedonic aroma, sugar formulation had a significant effect (P0.05) P0.05) on hedonic texture and had no significant effect (P0.05) on hedonic colour and taste. The best treatment was obtained from the G2N2 sample with salivary bacterial growth of 34.50 6.02 colonies and an overall hedonic value of 3.05 (likes).